2014
DOI: 10.1017/s0029665114000275
|View full text |Cite
|
Sign up to set email alerts
|

The role of polyphenols in the development of colorectal cancer: a systematic review and meta-analysis of case-controlled studies

Abstract: Polyphenols may inhibit carcinogenesis through their antioxidant and anti-inflammatory properties.(1) While their efficacy has been explored in vitro, clinical evidence of their impact on human health is lacking. This study aims to systematically review case-controlled studies examining dietary intake of polyphenols and the development colorectal cancer (CRC).MEDLINE, EMBASE, Web of Science, CABI, BIOSIS, CINAHL, DARE, TRIP & CDSR were searched using a predefined search strategy including 52 polyphenolic compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…In a meta-analysis of 18 randomised clinical trials [3], flavonol intake, mainly quercetin, reduced total cholesterol, triacylglyceride (TAG), low-density lipoprotein (LDL), systolic blood pressure (SBP), diastolic blood pressure (DBP) and increased high-density lipoprotein (HDL) levels. A meta-analysis of seven case-control studies showed an inverse association between flavonol and procyanidin intake and development of colorectal cancer [4].…”
Section: Introductionmentioning
confidence: 99%
“…In a meta-analysis of 18 randomised clinical trials [3], flavonol intake, mainly quercetin, reduced total cholesterol, triacylglyceride (TAG), low-density lipoprotein (LDL), systolic blood pressure (SBP), diastolic blood pressure (DBP) and increased high-density lipoprotein (HDL) levels. A meta-analysis of seven case-control studies showed an inverse association between flavonol and procyanidin intake and development of colorectal cancer [4].…”
Section: Introductionmentioning
confidence: 99%